The Methodology Employed by Ahl al-Sunnah Wa al-Jama‘ah When Confronting Contemporary Challenges to Islamic Thought (Contrarius Series: Law & Social Justice, 2026)
This study examined the role of Ahl al-Sunnah wal-Jama‘ah (ASWJ) in addressing contemporary challenges faced by Islamic thought as well as efforts to safeguard the integrity of the Islamic faith. This qualitative study analysed by using inductive, deductive and comparative methods. Findings indicate that ASWJ plays a crucial role in countering deviant ideologies and distorted interpretations through three key principles, namely strengthening faith (aqīdah) by understanding the 20 Attributes (Sifat 20), integrating rational (‘Aqlī) and divine (naqlī) arguments and applying the (Wasatiyyah) moderation arguments to refute misconceptions about Islamic teachings. Ultimately, the reaffirmation of ASWJ principles serves as the foundational core in the Usuluddin discipline, thus ensuring that Islamic theology remains grounded in divine revelation (wahy), rational reasoning (ʿaql), and spiritual purification (tazkiyah al-nafs) when confronting the complexities of contemporary thought.